An Economic Analysis of the Production Behaviour of Fishing Firms in Selected Fisheries of Malaysia. - Alam, Md. Ferdous (1991)
An import an t problem in the fishing industry of Peninsular Malaysia is the existence of grouprivalry and conflict between art is anal fishermen and trawlers resulting from the common property nature of fishery. This has led to overfishing in the inshore waters affecting both the catch and income of a large majority of artisanal fishermen. The present system of distributing marine earnings which favours boat owners further aggravates the problem of poverty among fishermen. This study examines the distribution of marine earnings, costs and returns of the fishing operations for three gears namely, trawl, purse seine and gill net, and the structure of their respective harvesting technologies. The general objective is to study the production behaviour of the relevant fishing firms and the specific objectives include the study of supply response to changes in fish prices, input demand response to changes in fact or prices, and cross supply and demand responses to changes in output-input prices. The nature of the share systems in marine fishing and the extent of their variations across boats and locations is also examined. The study also attempts to determine whether the observed vessel sizes are in long-run equilibrium.